1992
DOI: 10.1139/f92-077
|View full text |Cite
|
Sign up to set email alerts
|

Large Woody Debris and Salmonid Habitat in a Small Coastal British Columbia Stream

Abstract: Sections of a small coastal British Columbia stream that had previously been cleaned of large woody debris (LWD) were compared with sections where most debris was left and with others where debris had been relatively undisturbed for at least 40 yr. Three sections where debris had been removed had simple habitat that was less sinuous, wider, and shallower and had less pool volume and overhead cover than four sections with more complex habitat where debris was retained. Habitat in four relatively undisturbed sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
215
5
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(227 citation statements)
references
References 0 publications
4
215
5
3
Order By: Relevance
“…However, in most field studies where confounding factors are numerous, it has been found that the presence of cover has no (SAUNDERS and SMITH, 1962;FAUSCH and NORTHCOTE, 1992;FAUSCH et al, 1995;FLEBBE and DOLLOFF, 1995;GOWAN and FAUSCH, 1996;HARVEY, 1998) or even a negative effect (WILZBACH et al, 1986) on growth although increased growth rates are sometimes attributed to the presence of rootwad cover (NIELSEN, 1992) or riparian cover (VILA-GISPERT et al, 2000). Results obtained in laboratory experiments are also equivocal due to difficulties in defining working hypotheses and to methodological problems (e.g.…”
Section: Effects Of Cover Structures On Biological Productivitymentioning
confidence: 99%
“…However, in most field studies where confounding factors are numerous, it has been found that the presence of cover has no (SAUNDERS and SMITH, 1962;FAUSCH and NORTHCOTE, 1992;FAUSCH et al, 1995;FLEBBE and DOLLOFF, 1995;GOWAN and FAUSCH, 1996;HARVEY, 1998) or even a negative effect (WILZBACH et al, 1986) on growth although increased growth rates are sometimes attributed to the presence of rootwad cover (NIELSEN, 1992) or riparian cover (VILA-GISPERT et al, 2000). Results obtained in laboratory experiments are also equivocal due to difficulties in defining working hypotheses and to methodological problems (e.g.…”
Section: Effects Of Cover Structures On Biological Productivitymentioning
confidence: 99%
“…Large wood (LW) (41 m length  10 cm diameter) increases habitat heterogeneity by facilitating pool formation, altering stream flow, stabilizing banks, and retaining sediment and coarse organic matter (Gippel 1995;Kail 2002;Cordova et al 2007). Increased habitat complexity can increase fish species richness, density and biomass (Faush and Northcote 1992;Cederholm et al 1997;Harvey et al 1999). Several studies have shown that fish abundance and biomass increased with increased levels of in-stream LW (Probst et al 1984;Warren et al 2000) or as pools formed by LW increased (Faush and Northcote 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Increased habitat complexity can increase fish species richness, density and biomass (Faush and Northcote 1992;Cederholm et al 1997;Harvey et al 1999). Several studies have shown that fish abundance and biomass increased with increased levels of in-stream LW (Probst et al 1984;Warren et al 2000) or as pools formed by LW increased (Faush and Northcote 1992). In addition, pooling of water by LW can provide refuge for fish during high flow or from predators (Warren et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…These physical processes are especially important when considering streams which in order to support fish must exhibit clear, cool water and an array of morphological complexity Bjornn and Reiser, 1991;Fausch and Northcote, 1992). For some species, such as salmonids, spawning and incubation requires riffles and runs composed predominantly of larger sediment, with interstices free offine sediments (Bjornn and Reiser 1991).…”
Section: Riparian Zones and Morphological Processesmentioning
confidence: 99%
“…Further, it is the diversity of microhabitat that creates conditions necessary 20 to allow the co-existence of multiple species commw1ities (Bisson et al, 1982;Hicks et al, 1991 b). The microhabitat caused by L WD contributes to fish survival by providing quality foraging areas, velocity refuges, increased depth and cover from predators (Toews and Moore, 1982;Elliot, 1986;Shirvell, 1990;McMahon and Holtby, 1992;Fausch and Northcote, 1992).…”
Section: Riparian Zones and Morphological Processesmentioning
confidence: 99%